Evaluation of the efficacy of casein phosphopeptide-amorphous calcium phosphate on remineralization of white spot lesions in vitro and clinical research: a systematic review and meta-analysis - Xueling Ma; Xuandong Lin; Tengfei Zhong; Fangfang Xie (BMC, 2019)
Abstract Background This systematic review with meta-analyses sought to answer whether casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) provided a remineralizing benefit superior to that of nonintervention or placebo. Methods Following Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines, Cochrane databases, PubMed, EmBase, and Ovid up to May 20th, 2019, were scanned, only published in English. Study information extraction and methodological quality assessments were accomplished independently by two reviewers. The "Criteria for judging risk of bias in the 'Risk of bias' assessment tool" was used for methodological quality assessment. The continuous data was analyzed by mean difference (MD) or standardized mean difference (SMD) with a 95% confidence interval (CI). Review Manager 5.3 was used for statistical analysis. Outcome variables include quantitative light-induced fluorescence in clinical research, average surface roughness and surface microhardness in vitro. Results There were significant differences in the quantitative light-induced fluorescence (SMD = − 0.43, 95% CI: [− 0.79, − 0.07], P = 0.02), average surface roughness (SMD = − 8.21, 95% CI: [− 10.37, − 6.04], P < 0.01), Vickers microhardness (SMD = 1.19, 95% CI: [0.72, 1.66], P < 0.01), and Knoop microhardness (SMD = 3.52, 95% CI: [2.68, 4.36], P < 0.01) between the CPP-ACP and control groups or baseline. Conclusion Within the limitations of this meta-analysis, CPP-ACP exhibited excellent remineralization effects evaluated in clinical research and in vitro, indicating outstanding restoration of form, aesthetics, and function in treating white spot lesions.